Cell Apoptosis of Monocyte-Phagocyte System and Mechanisms for Its Regulation - Goltsev, A. N.; Yampolskaya, E. E. (Problems of Cryobiology and Cryomedicine, 2006)
Apoptosis was established to play a significant role in maintaining cell and tissue homeostasis. Data on cell sensitivity of monocyte-phagocyte system to apoptosis induction are contradictory, therefore of interest is to reveal the way of realising in them the mechanism of apoptotic program and factors affecting apoptotic process in cells of this system. Nowadays there has been actual the search for new ways using which we could control apoptotic processes, as well as correct the balance of pro- and anti-apoptotic molecule content. The most perspective products with such an ability are those of embryofetoplacental complex since they harmonise the mechanisms of interactions between cells in structures of neuroimmunoendocrine block, responsible for maintaining bodyhomeostasis in a recipient’s organism.